Does the poor use of attentional skills affect academic performance? - Tatoy, Froilan Jr. C. (1999)
The phenomenon of learning is significantly related to the use of attentional skills. To substantiate this hypothesis, the researcher conducted a study examining the relationships between academic performance and the use of attentional skills by specifically delving into the difference between the academic performances of the pupils who use attentional skills effectively and those who poorly utilize it. From the data collected and the corresponding statistical analysis, the researcher arrived at the conclusion that there is a significant difference between the academic performances of the two groups of subjects. It was manifested by the remarkable discrepancy between the values of t (4.37) and df (2.201) obtained from the use of T- test statistical method reflected on the results. Hence, this study proves that the poor use of attentional skills contribute to poor academic performance.
Undergraduate thesis (B.A.S.S. Psychology) -- University of the Philippines, Tacloban.
Keywords: Academic performance